2021
DOI: 10.26480/aim.02.2021.62.70
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Effects of Social Media Cyberbullying on Students in Selected African Countries

Abstract: This study investigates the psychosocial impact of cyberbullying on social media among students in Nigeria, Ghana, Zimbabwe, and Cameroon. The study adopted a quantitative research methodology in collecting data from 99 students across the selected African countries using a well-designed electronic questionnaire (e-questionnaire). The study found that cyberbullying on social media has psychosocial implications for the student. Furthermore, the study revealed ways and strategies to mitigate the spread and act o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
7
1
4
Order By: Relevance
“…Penelitian lainnya mengemukakan bahwa terdapat hubungan antara penggunaan media sosial dengan perilaku Sendiri Saat Bersama (Setiadi, Devitoyani, & Andi, 2021). Temuan pada studi lainnya mengungkapkan bahwa media social memberdayakan siswa untuk memahami bahwa platform media sosial, mempromosikan interaksi sosial, tetapi mendorong jarak fisik antara teman-teman dalam pertemuan atau acara (Chukwuere, 2021). Donlevie mengemukakan terdapat hubungan yang positif namun lemah antara penggunaan media sosial dan interaksi sosial secara langsung.…”
Section: Pendahuluanunclassified
“…Penelitian lainnya mengemukakan bahwa terdapat hubungan antara penggunaan media sosial dengan perilaku Sendiri Saat Bersama (Setiadi, Devitoyani, & Andi, 2021). Temuan pada studi lainnya mengungkapkan bahwa media social memberdayakan siswa untuk memahami bahwa platform media sosial, mempromosikan interaksi sosial, tetapi mendorong jarak fisik antara teman-teman dalam pertemuan atau acara (Chukwuere, 2021). Donlevie mengemukakan terdapat hubungan yang positif namun lemah antara penggunaan media sosial dan interaksi sosial secara langsung.…”
Section: Pendahuluanunclassified
“…Dan juga rentan bagi remaja atau siswa menjadi korban cyberbullying atau perundungan dan kekerasan online, pelanggaran informasi pribadi dan lainnya. 23 Diketahui bahwa remaja atau siswa di berbagai sekolah yang ada di Indonesia lebih cenderung nyaman berinteraksi sosial kepada teman-temanya dengan menggunakan media sosial. Padahal remaja atau siswa perlu diarahkan untuk terlibat dalam komunikasi langsung dalam meningkatkan intensitas pertemanan atau sosialnya.…”
Section: Aulia Iswaratamaunclassified
“…However, the focus of this study is on tertiary students between the ages of 19 and 25. Studies have shown that the use of social media had grown concerns from different people regarding its potential addiction, bullying, and effects on students globally (Moyo & Abdullah, 2013 cited in Chukwuere et al, 2021). Notwithstanding the possibility of affecting academics positively and the improvement of experience, its continuous usage leads to addictions.…”
Section: Overview Of Cyberbullyingmentioning
confidence: 99%